Bayes estimators for the parameters of truncated Campbell distribution using Lindley's approximation (Statistics, Optimization & Information Computing, 2025)
In this research, the Campbell distribution (maximum value) was truncated by deleting a part of the distribution domain so that the distribution function maintains its probability properties, to obtain the truncated Campbell distribution (maximum value) (TC). Also, the maximum likelihood function (MLE) and Bayes estimators for the scale and location parameters were derived using Lindley approximation with taking different loss functions, which are the squared loss function (SEL) and the general entropy function (GEL). We also used the simulation method to generate many sample sizes (n= 10, 60, 120, 150) with many different values ​​of the scale parameter and the location parameter, and the estimators were compared using the mean square error (MSE) measure.